English Learning Styles of the Eleventh Grade Students in SMA Negeri 07 Kendari - Azwan Hepriansyah (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2023)
This study aimed to find out the English learning styles of the eleventh-grade students in SMA Negeri 07 Kendari and the contribution of students learning styles to English achievement. Those learning styles were visual, auditory, read/write, and kinesthetics. This study applied a quantitative approach under the survey research design. The sample for this study was 84 students of grade 11 in SMA Negeri 07 Kendari, who were divided into 4 classes. A closed-ended questionnaire was used to collect the data. This study used descriptive statistics and simple linear regression to analyze the data. The results of this study showed that the majority of grade 11 students in SMA Negeri 07 Kendari used auditory learning as their major English learning style preference. Meanwhile, visual learning was their minor English learning style preference. Followed by read-write and kinesthetics learning styles. There was a significant relationship between the students’ learning styles and their English achievement, with the significance value (Sig.) being 0.000 smaller than the probability of 0.05, and the contribution of the students’ learning styles to the English achievement of the eleventh-grade students in SMA Negeri 07 Kendari was 30%. The R square value is 0.300. It means that learning style is not the main factor contributing to the students’ academic achievement. _________________________________________________________________________________________________________________________________________ Penelitian ini bertujuan untuk mengetahui gaya belajar bahasa Inggris siswa kelas sebelas di SMA Negeri 07 Kendari dan kontribusi gaya belajar siswa terhadap prestasi bahasa Inggris. Gaya belajar tersebut adalah visual, auditori, baca/tulis, dan kinestetik. Penelitian ini menerapkan pendekatan kuantitatif dengan desain penelitian survei. Sampel penelitian ini adalah 84 siswa kelas 11 SMA Negeri 07 Kendari yang terbagi dalam 4 kelas. Kuesioner tertutup digunakan untuk mengumpulkan data. Penelitian ini menggunakan statistik deskriptif dan regresi linier sederhana dalam menganalisis data. Hasil penelitian ini menunjukkan bahwa mayoritas siswa kelas 11 SMA Negeri 07 Kendari menggunakan pembelajaran auditory sebagai preferensi gaya belajar bahasa Inggris utama mereka. Sementara itu, pembelajaran visual merupakan preferensi gaya belajar bahasa Inggris minor mereka. Dilanjutkan dengan gaya belajar baca/tulis dan kinestetik. Terdapat hubungan yang signifikan antara gaya belajar siswa dan prestasi bahasa Inggris mereka, dengan nilai signifikansi (Sig.) sebesar 0,000 lebih kecil dari probabilitas 0,05, dan kontribusi gaya belajar siswa terhadap prestasi bahasa Inggris siswa kelas sebelas di SMA Negeri 07 Kendari sebesar 30%. Nilai R Square sebesar 0,300. Artinya, gaya belajar bukanlah faktor utama yang berkontribusi terhadap prestasi akademik siswa.